UPAYA PENINGKATAN KEMAMPUAN MENYAMPAIKAN ISI BERITA DI SURAT KABAR MELALUI METODE DRILL SISWA KELAS VI SD NEGERI 011 PAGARAN TAPAH DARUSSALAM - Afrianti Afrianti (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
This research is motivated by the lack of ability to deliver the news in the newspaper six graders SD Negeri 011 Pagaran Tapah Darussalam, this study aims to determine whether through the use of drill can improve the students' sixth grade in SD Negeri 011 Pagaran Tapah Darussalam to deliver the news in a letter news in the field of Indonesian studies, conducted during one month. As the subjects in this study were students of class VI 2015-2016 school year the number of students 11 people, consisting of 7 students male and 4 female students. Form of research is classroom action research. The research instrument consists of instruments and instrument performance data collection activity observation sheet form teacher and student activity. Based on the research that has been done, then the conclusion to this study about upgrading deliver news content in newspapers through drill method grade VI SD Negeri 011 Pagaran Tapah Darussalam. The average value of the ability of students before the first cycle of 44.3 in the first cycle, amounting to 60.2 and the second cycle at 79.2 or capability that is expected to have reached as many as more than 70% of students scored at the top of the KKM is 70. The above statement shows that the ability to deliver the news in the papers can be enhanced through drill method.